O Fogo do Amor - Mohammed Rustom (Horizonte)
Tradução que se encontra em: Rustom, Mohammed. Theo-Fānī: ʿAyn al-Quḍātand the Fire of Love. In: ORFALI, Bilal; KHALIL, Atif; Rustom, Mohammed. Mysticism and Ethics in Islam. Beirut: American University of Beirut Press, 2022, p. 129-138